Memahami Konsep Manajemen Layanan Konsultasi dalam Bimbingan Konseling - Bakhrudin All Habsy; Maunatus Silviana; Mutiah Nur Zaliha; Renovaliano Firdiansyah (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study aims to examine how systematic guidance and counseling services are implemented, in accordance with the management planning and adjustments that exist in the field, school environment, or community. This study uses a descriptive approach with a literature study method. The results of the study show that guidance and counseling services have an important role in student development. The concept of consultation services in guidance and counseling is explained in detail, including the objectives, models, and stages of implementation. The study also underlines the importance of planning, organizing, implementing, supervising, and evaluating in the management of guidance and counseling services. The results of this study are expected to contribute to the development of more effective and efficient guidance and counseling services in schools.